Klasyfikacja polskich dwuczłonowych compositów o członach inicjalnych mało- i wielo-. Studium słownikowe - Machowski, Szymon (Investigationes Linguisticae, 2011)
The aim of this article is to suggest a new classification of the Polish compound words with the initial constituents mało- and wielo-. The study is based on the corpus of such compound words extracted from the Universal Dictionary of Polish Language PWN edited by S. Dubisz. The criterion of classifying the analyzed compound words is a semantic accordance between the parathesis of the compound words and their Polish equivalents. Based on the criterion above the analyzed compound words have been divided into 3 groups.